2008
DOI: 10.1248/bpb.31.1574
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Delivery of Insulin Using Trypsin as a Biochemical Enhancer

Abstract: There are 30 million patients with diabetes mellitus worldwide, and 1.2 million new patients are diagnosed each year, including a growing number of children and young adults. 1)However, insulin has been administered only by parenteral routes for the therapeutic control of type 1 diabetes; many patients typically require injections of insulin a minimum of two to three times per day. To improve patient convenience and compliance, alternative routes have been investigated including nasal, oral, transdermal, bucca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Trypsin enhanced the penetration of insulin, resulting in reduction of blood glucose levels in rats. [186] Mechanistic studies suggested that trypsin could disturb the structure of keratin in the SC via proteolysis but appeared to have no effect on the lipid bilayers. [186] Trypsin can also enhance the transdermal permeation of other macromolecules such as FITC-labelled dextrans and FITC-insulin.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…Trypsin enhanced the penetration of insulin, resulting in reduction of blood glucose levels in rats. [186] Mechanistic studies suggested that trypsin could disturb the structure of keratin in the SC via proteolysis but appeared to have no effect on the lipid bilayers. [186] Trypsin can also enhance the transdermal permeation of other macromolecules such as FITC-labelled dextrans and FITC-insulin.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…Many scientists have taken up the challenge of developing a transdermal DDS for insulin. [22][23][24][25] Iontophoresis is a powerful device for the transdermal delivery of poorly permeable drugs. TDDS have already been developed for lidocaine and are now used clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Endmember 5 has high abundances in the periphery of the mapped area and shows a relatively high amount of lipid, as indicated by the strong band at 1744 cm À1 , assigned to ester carbonyl mode of lipids [30,31]. It also naturally has a large amount of protein, as evinced by the intensity of the bands at 1648 and 1532 cm À1 [3,28,32].…”
Section: Overall Morphology and Protein Distribution According To Ir mentioning
confidence: 99%